Theoretical Study for a Solar Powered Desalination Unit using Humidification –Dehumidification Technique - Abdulghani M. Ramadan; Mabrouk Algamil (Solar Energy and Sustainable Development, 2017)
A solar powered desalination unit which is working on a humidification –dehumidification technique (HDH) is one of the most important techniques used in seawater desalination in remote and rural areas. It is easy to design, operate and maintain. In this paper, a theoretical study based on a design methodology for a solar assisted desalination unit working on a HDH principle under the prevailing conditions of Tajoura-Libya is carried out. The main target is to study the effect of different design and operating parameters that influence the performance of the unit and its productivity under different design scenarios; (spring, summer, autumn and winter). Results show that the productivity of the unit is increased with a corresponding increase in the inlet air mass flow rate to the solar air heater, inlet water mass flow rate to the humidifier and cooling water mass flow rate to the dehumidifier. A significant increase in the productivity of the unit is achieved when the initial water temperature and the initial mass of water inside the storage tank were increased. Moreover, Gained Output Ratio, GOR, values vary between (0.27 and 0.79) for winter and spring designs and (1.94 and 2.75) for autumn and summer designs respectively. In general, the productivity of the unit is estimated to be within a range from a minimum of (2 ~ 4) kg/m2.day, in winter to a maximum of (10 ~ 12) kg/m2.day, in summer, which makes it very convenient for using in rural and remote areas.